The Influence Of Self Regulation And Organizational Culture On Organizational Commitment Among Police Members At Satlantas Polres Ketapang, West Kalimantan - Angga Aristya; Irfan Mahdi (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2025)
This study investigates the influence of Self Regulation and Organizational Culture on Organizational Commitment among members of the police force at Satlantas Polres Ketapang, Kalimantan Barat. Using a sample of 56 respondents, data were collected using structured questionnaires. Statistical analyses including correlation, regression, and reliability tests were conducted to assess the relationships and predictive power of the variables. Findings reveal significant positive correlations between Self Regulation, Organizational Culture, and Organizational Commitment. Regression analysis indicates that Self Regulation and Organizational Culture collectively explain 21.0% of the variance in Organizational Commitment. These results underscore the importance of fostering self-regulation practices and nurturing supportive organizational cultures to enhance organizational commitment within law enforcement agencies. The study contributes to understanding organizational behavior within policing contexts and suggests practical implications for organizational development strategies.